Report of the Study Group on Parameters of Consumption Sub-Model - Planning Commission (Planning Commission, 1991)
The Study Group Report on Parameters of the Consumption Sub-Model, released by the Planning Commission of India in 1991, examines and revises the framework for analyzing private consumption in India. Using National Sample Survey data and a Linear Expenditure System, the study re-estimates demand parameters across income groups and commodity categories for both rural and urban populations. The report highlights variations in consumption patterns, demand elasticities, and expenditure behavior with rising income levels. It emphasizes the declining share of food in total consumption as incomes increase and underscores the need for flexible, updated modeling approaches. The findings provide important inputs for consumption projections and policy formulation, particularly in the context of the Eighth Five-Year Plan.
Perspective Planning Division Government of India, Planning Commission, New Delhi, March 1991
Perspective Planning Division Government of India, Planning Commission, New Delhi, March 1991
Keywords: Private Consumption; Linear Expenditure System; National Sample Survey; Demand Elasticities; Consumer Behavior; Income Groups; Commodity Classification; Econometric Analysis; Eighth Five Year Plan; Consumption Projections